Why is PayLater Scheme via E-commerce Prohibited in Islam? Islamic Law Overview - Nur Rizqi Febriandika; Ahmad Syaifuddin; Aminudin Ma'ruf (Fakultas Hukum Universitas Muhammadiyah Magelang, 2022)
The internet has now been used as a medium for Online shopping; one of the media for Online shopping is e-commerce. Currently, a delayed payment system (debt) called PayLater has been implemented in e-commerce. The purpose of this study is to find out how the usage of PayLater in e-commerce is based on the perspective of Islamic law. This type of research is qualitative. Data collection methods used are library research, observation, and interviews. This study uses descriptive data analysis techniques, namely analyzing a phenomenon or social reality, by describing variables that are concerned with the problem and unit being studied and analyzed descriptively qualitatively using an inductive thinking approach, namely a way of thinking that departs from facts, events that occur. Then from the specific and concrete facts, generalizations that have a general nature are drawn. The results of the study prove that the law of buying and selling online according to Islamic law is valid as long as it does not contain haram elements and the goods being traded are halal. However, the practice of PayLater loans is not in accordance with Islamic law because there is an element of usury contained in it.